Water salinity monitoring of paddy field in Kampung Sempang and Pengkalan Samak at Merlimau, Melaka / Mohammad Shamsul Sabran - Sabran, Mohammad Shamsul (Faculty of Plantation and Agrotechnology, 2019)
Cyberscan 600 siries meter is a technology of tool that using to determine and measure the water elements. This case study is focus on analysis and measure the water salinity rate that contains in the river of paddy (Oryza sativa) field at Merlimau area. Location I’ve chosen for this study are two location which is Kampung Sempang and Pengkalan Samak at Merlimau, Malacca. This tool just uses for water sample that taken from some river near paddy field. There are several elements can measure by Cyberscan tool such as water salinity rate, resistivity, water pH, suspended solid, total dissolved solids, and others. All result from Cyberscan reading can print out and transfer the data into computers. Generally, this tool for monitoring any elements contain in the water. This operation facilitates to researcher and farmers to identify water source problem and any else. The price of Cyberscan Siries 600 up to RM12,100 per unit. Besides, this tool very useful for customer like researcher, farm development and farmers. This tool was established in 1990 and certified by Eutech Instruments company. The dedicated to the design and manufacture of sensor-based instruments for water quality analysis for develop the plantation industry. This tool also can help the smallholders of plantation industry to rise the production of crop cultivation.